P–579 Pregnancies following preimplantation Genetic Testing have an increased risk for post-partum complications. (6th August 2021) - Srebnik, N; Rotem, R; Sverdlik, Y; Amosi, D Victo; Dekel, N; Rotshinker, K; Eldar-Geva, T; Be. Ami, I; Shonberger, O; Michaeli, J
Abstract: Study question: Do preimplantation genetic testing (PGT) pregnancies have higher pregnancy and delivery complications compared to naturally conceived (NC) pregnancies? Summary answer: PGT pregnancies do not have increase pregnancy complications but do have increased post-partum complications. What is known already: There is limited data about the outcome of PGT cycles regarding pregnancy complications. Previous reports show that PGT pregnancies are similar to NC pregnancies regarding birth weight and preterm delivery rate. Patients performing PGT are less likely to have infertility as a background problem, and therefore it is important to evaluate pregnancy complications in this specific population. Study design, size, duration: A retrospective cohort study, between 2008–2020 in Shaare Zedek Medical center (SZMC). Demographic, background variables, treatment cycle information, and delivery data were collected from computerized hospital databases and patient files. Participants/materials, setting, methods: All patients aged 18–45 that conceived following PGT treatment in the IVF unit and gave birth in SZMC were included in the study. We used two control groups: (1) women with spontaneous pregnancies (SP) who gave birth in SZMC. We used four "neighborhood control" for each PGT patient (two women delivered before and two after the case delivery). (2) pregnancies following ICSI with four neighborhood control for each. Main results and the role of chance: 135 deliveries following PGT, 924 ICSI, and 4199 NC. Demographic variables were similar except PGT, and ICSI women were slightly older (30.93 ±4.33 PGT, 31.70±4.98 ICSI, 28.75±5.69 spontaneous, p < 0.01). PGT pregnancies had similar rates of placental complications (hypertensive disorder, preeclampsia (PET), placental abruption) as NC (p = 0.8), while ICSI pregnancies had significantly higher rates of gestational hypertension (p < 0.01) and abruption (p = 0.05). We found a higher rate of preterm delivery <37 weeks in both PGT and ICSI pregnancies (23.7%, 22.7%, 12.1%, p < 0.01 for PGT, ICSI, NC respectively), but only in ICSI was preterm delivery < 34 weeks increased (2.2% vs. 2.1%, p = 0.9, for PGT and NC, 4.3% for ICSI p < 0.01). Post-partum complications were more prevalent in both PGT and ICSI: longer third stage of labor (13.27±12.81, 12.58±10.08, 10.58±8.14, p < 0.05), manual lysis of placenta (6.7%, 2.3%, 1.4% p < 0.05), post-partum hemorrhage (PPH) (5.9%, 4.2%, 2.5% p = 0.02) and need for blood products (3.7%, 4.5%, 1.3% p = 0.02) for PGT, ICSI, NC respectively. The aOR for composite post-partum complications (PPH, hemoglobin drop>3 gram, revision or lysis) was 2.4, 95%CI [1.6–3.7]. We did not find any difference between fresh and frozen cycles in either placental complications, preterm delivery, or post-partum complications in the PGT group. Limitations, reasons for caution: A single-center retrospective study. Included only pregnancies both conceived and delivered in SZMC. Wider implications of the findings: Physicians should be aware of PGT pregnancies as risk factors for post-partum placental complications and handle the third stage of the delivery with caution. Trial registration number: 0351–18-SZMC